Identifying soil quality indicators for two contrasting agro-ecological sub-regions of India. Issue 1 (2nd January 2023) - Chandran, Padikkal; Vasu, Duraisamy; Tiwary, Pramod; Karthikeyan, Karunakaran; Jangir, Abhishek; Tiwari, Gopal; Paul, Ranjan; Das, Krishnendu
ABSTRACT: This study aims to identify soil quality indicators, assess soil quality index (SQI), and validate them with crop yield for India's two contrasting Agro-ecological Sub-Regions (AESRs). For this, 340 and 85 soil samples (0–15 cm) from AESRs 6.1 (semi-arid dry) and 18.4 (sub-humid dry) were analysed for 26 soil physical, chemical, and biological properties. Principal component analysis (PCA) was used to identify soil quality indicators, and the SQI and relative SQI (RSQI) were calculated using the weighted index method. We identified soil pH, active carbon pool (ACP), and available Zn as common indicators for both the AESRs apart from specific indicators. The SQI of AESR 6.1 soils under cotton and sugarcane were higher (0.48–0.75) than the AESR 18.4 soils under rice (0.26–0.70). Among the indicators, EC (35%), CEC (24%), pH (23%), clay (17%), and ACP (14%) significantly contributed to the SQI. The strong relationship of RSQI with the yield of cotton (R 2 = 0.52), sugarcane (R 2 = 0.68), and rice (R 2 = 0.64) indicated that the selected indicators are representative to measure soil quality. We conclude that AESR specific soil quality indicators are appropriate for the evaluation and monitoring of agroecosystem functions.